The land use consequences of rural to urban migration* - Brewer, Julia; Larsen, Ashley; Noack, Frederik (American Journal of Agricultural Economics, 2024)
Rural to urban migration (RUM) is a key component of economic development, but its environmental consequences are not well understood. Here, we study the impacts of RUM on agriculture and land use using household panel data in combination with tree cover data from Uganda. Our results show that the labor loss and the inflow of remittances from RUM lead to a reduction in crop diversity but no shift toward less labor-intensive crops or crops with a high up-front investment. In addition to those results at the intensive margin, we find a reduction of cultivated area at the household level, which translates into reduced tree cover loss at the district level. These results suggest an important but nuanced role of RUM for land use change.
Keywords: Agriculture; Deforestation; Environment; Land Use; Remittances; Migration